Control of ribosome turnover during growth of the haloalkaliphilic archaeon Natronococcus occultus - Nercessian, Debora (2006)
The metabolism of ribosomes during growth of the haloalkaliphilic archaeon Natronococcus occultus was examined. The ribosome content was higher during exponential growth and diminished to 35% of the maximum in the stationary stage. The incorporation of 3H-orotic acid and 14C-uracil into rRNA was higher during exponential growth. After that, it decreased to 39% of the maximum in the stationary stage. The labeling of non-ribosomal RNA took place almost exclusively in the exponential stage. From loss of radioactivity, the half-life of rRNA was 11.43, 14.85, 5.28 and 7.14 h during the initial, exponential, late exponential and stationary growth stages, respectively. These results suggested that increased synthesis combined with diminished degradation were responsible for the high ribosome content displayed by Ncc. occultus during exponential growth. In contrast, diminished synthesis together with increased degradation provoked its posterior loss.